2001
DOI: 10.1103/physrevlett.87.197004
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Enhanced Superconductivity in Metals near the Metal-Insulator Transition

Abstract: We have studied the transport properties of disordered WSi films near the metal/insulator transition (MIT) and we have also reviewed the data for several other disordered materials near their MIT. In all cases, we found the presence of enhanced superconductivity. We constructed a superconductivity "phase diagram" (i.e., T(c) versus sigma) for each system, which reveals a striking correlation: In all cases, T(c) values are significantly enhanced only for samples whose conductivities lie within a narrow range on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 31 publications
5
45
0
Order By: Relevance
“…33 All the above results suggest that superconductivity in W alloys films, regardless of the fabrication method, is attributed to their amorphous structure which is promoted by C, Si, and Ge impurities. This conclusion is further supported by Osofsky et al 37 model which relates this enhancement in T c to the level of disorder (i.e. resistivity) near the metal-insulator transition of the films.…”
supporting
confidence: 71%
“…33 All the above results suggest that superconductivity in W alloys films, regardless of the fabrication method, is attributed to their amorphous structure which is promoted by C, Si, and Ge impurities. This conclusion is further supported by Osofsky et al 37 model which relates this enhancement in T c to the level of disorder (i.e. resistivity) near the metal-insulator transition of the films.…”
supporting
confidence: 71%
“…We therefore speculate that the enhanced T c in our thinnest films arises due to the reduced electron mean-free-path. Osofksy et al [11] have previously demonstrated that, near the MIT, reducing the mean-free-path leads to an increase in the electron screening length which in turn leads to an increase in the BCS electron-phonon interaction potential.…”
Section: Resultsmentioning
confidence: 99%
“…Such a view, where both l and m à are rescaled by the proximity of the metal-to-insulator transition (MIT), is not so common although the influence of the proximity of the MIT on the superconducting behaviour of disordered metals has been studied extensively in order to explain the enhancement of T c in the vicinity of the MIT (Osofsky et al 2001(Osofsky et al , 2002Soulen et al 2003). Such an enhancement has not been reported for diamond so far.…”
Section: Doping-induced Normal-to-superconducting Transitionmentioning
confidence: 96%